ANALISIS KELAYAKAN MENERIMA PINJAMAN KREDIT DENGAN ALGORITMA C4.5 PADA PT. BPR BUANA ARTA MULIA - David; Elisa, Erlin (LPPM Universitas Putera Batam, 2022)
Credit is one of the easiest alternative solutions for those who need financial support, either to be used to meet consumptive needs, as business capital or for other purposes. With credit assistance, people's living standards will be better and other needs that could not be realized before can be fulfilled to the fullest, which makes many people choose credit as a solution for funding needs. PT BPR Buana Arta Mulia is a banking company which one of its operational activities is to provide services for providing funds or credit loans to prospective debtors, problems that are still often faced by banks so far are regarding arrears made by debtors and several cases related to bad loans. So far, the bank has a collection of data regarding the credit application history of prospective debtors that has not been used optimally so that the author intends to conduct an analysis of the data to find out the hidden rules in determining the feasibility of receiving credit loans with the aim of improving the quality of the credit analysis results as well as an evaluation material for determining creditworthiness in the future. In this study, data mining classification techniques will be used with the C4.5 algorithm model in carrying out the analysis process and to ensure the correctness of the decisions obtained through manual calculations, testing will be carried out using the WEKA 3.9.5 software. the results of the rules generated either from manual calculations or using WEKA are the same and from the results obtained indicate that there are two variables that have the most influence in determining creditworthiness, namely from collateral value and income variables.